2020
DOI: 10.24018/ejedu.2020.1.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Geometer’s Sketchpad on Senior High School Students’ Performance in Quadratic Graphing

Abstract: Arguably the teaching and learning of algebra in schools have been perceived as difficult (Looney, 2004) at all levels due to the non-usage of modern technology, especially in Africa. This study sought to explore how the geometer’s sketchpad (GSP) could be used to improve students’ performance in quadratic graphs. The study employed true-experimental (Post-test) design as a strategy of enquiry using Geometer’s Sketchpad application software in which the mixed-method strategy was used in the sampling of the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(27 reference statements)
1
0
0
1
Order By: Relevance
“…Finally, the research revealed the academic achievement of senior secondary students who learned geometry using mathematical software is not dependent on gender. The result supports the earlier findings by [29] whose studies found that there is no interaction effect of the use of geometers' sketchpad and gender on SS1 students' achievement in geometry.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, the research revealed the academic achievement of senior secondary students who learned geometry using mathematical software is not dependent on gender. The result supports the earlier findings by [29] whose studies found that there is no interaction effect of the use of geometers' sketchpad and gender on SS1 students' achievement in geometry.…”
Section: Discussionsupporting
confidence: 92%
“…Model ini dipilih kerana keupayaannya untuk membangunkan modul pembelajaran yang mengintegrasikan penggunaan teknologi (Bujeng et al, 2019). Pembangunan bahan pembelajaran serta aktiviti yang mengintegrasikan teknologi dan media menggunakan model ASSURE (Baity Bujeng, 2019;Chu et al, 2021;Gyedu et al, 2020;Norbaizura Nordin et al, 2019;Punia Turiman et al, 2019;Ramadhani & Fitri, 2020;Rasdi et al, 2021).…”
Section: Reka Bentuk Kajian Pembangunanunclassified